Evaluation Of Land Cover Changes In Sultan Azlan Shah Dam Catchment Using Remote Sensing Techniques - Razak, Mohd Firdaus Abdul (2013)
The study deals with analyzing of the land cover change pattern in the Sultan Azlan Shah (SASD) catchment over a period of 14 years using updated remote sensing data. SPOT XS with acquisition date at 15 January 1996. SPOT 4 MS with acquisition date at 10 February 2002 and SPOT 5 MS with acquisition date at 20 February 2010 were used to generated land cover classification map. Unsupervised, supervised and hybrid classification methods were implemented in the classification process. A further post-classification processing was applied to the hybrid classification map which has produced the highest accuracy. Subsequently, post-classification comparison (PCC) was used to analyze the change in land cover. The results shows that using hybrid classification method produced highest overall accuracies for image 1996, 2002 and 2010 which were 77.60% ( =0.7267), 80.91% ( =0.7456) and 80.00% ( =0.7267).